The Relationship Between Competence, Motivation, and Organizational Culture on Sustainable Employee Performance: A Qualitative Model - Muhammad Tohir (Siber Nusantara of Economic and Finance Review, 2025)
This research is motivated by various scientific findings demonstrating that employee performance is a strategic factor in organizational success. This literature review aims to examine and synthesize concepts, theories, and previous research findings that discuss the relationship between competence, motivation, and organizational culture and employee performance. The method used is a literature review, examining various scientific sources, including textbooks, national and international journal articles, and academic documents relevant to the research topic. The analysis process involved grouping themes, comparing findings, and drawing conceptual conclusions to gain a comprehensive understanding. The review results indicate that competence plays a role in improving employee capabilities and work quality, motivation influences internal drive to achieve work targets, and organizational culture shapes values ​​and norms that guide work behavior. Overall, this literature review concludes that competence, motivation, and organizational culture are strongly linked and mutually supportive in improving employee performance.